1993
DOI: 10.1021/jf00032a006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of cholesterol by heating

Abstract: Oxidation of pure cholesterol during heating in an air oven at high temperature was studied. Cholesterol was virtually stable during heating at 100 OC for 24 h but was unstable at temperatures above 120 OC. In the heated cholesterol preparations, a number of oxidized derivatives were detected by a combination of thin-layer chromatography and capillary gas chromatography-mass spectrometry. Major oxidized sterols were 7a-hydroxycho1estero1, 7,3-hydroxycholestero1, 5a-epoxycho1estero1, 5,3-epoxycholesterol, chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 26 publications
6
51
1
9
Order By: Relevance
“…Regarding the OS of PS in vegetable oils, some aspects should be considered, such as the degree of unsaturation of the lipid fraction and the occurrence and type of antioxidants. Studies on the effects of co-oxidizing matrix lipids are controversial because some indicate that PS oxidation is enhanced by unsaturated lipids (Osada et al 1993), while others have shown that oxidation is more pronounced in saturated than in unsaturated lipid matrix (Lampi et al 2002). The high unsaturation level and tocopherols content of the lipid matrix, in SFO, might have a protective effect on PS oxidation.…”
Section: Impact Of Frying On the Total Amount Of Psmentioning
confidence: 99%
“…Regarding the OS of PS in vegetable oils, some aspects should be considered, such as the degree of unsaturation of the lipid fraction and the occurrence and type of antioxidants. Studies on the effects of co-oxidizing matrix lipids are controversial because some indicate that PS oxidation is enhanced by unsaturated lipids (Osada et al 1993), while others have shown that oxidation is more pronounced in saturated than in unsaturated lipid matrix (Lampi et al 2002). The high unsaturation level and tocopherols content of the lipid matrix, in SFO, might have a protective effect on PS oxidation.…”
Section: Impact Of Frying On the Total Amount Of Psmentioning
confidence: 99%
“…Analytical procedures for the determination of the extent of cholesterol oxidation in food, especially in heated and/ or stored foods with high cholesterol content, include capillary gas-chromatography (GC) García & Maraschiello, 1997), GC-mass spectrometry (GC-MS) (Park & Addis, 1986;Osada et al, 1993), and high performance liquid chromatography (HPLC) . GC has been used by several researchers because it allows the rapid separation and identification of up to 17 different oxysterols.…”
Section: Oxysterolsmentioning
confidence: 99%
“…A fritura aparentemente apresentava maior potencial para oxidação do colesterol porque a temperatura utilizada (140°C) é mais elevada que no cozimento (cerca de 100°C), aproximando-se da faixa de maior instabilidade do colesterol, 120 a 150°C [14,26]. No entanto, foi o processamento que levou à maior redução nos ní-veis de 7-cetocolesterol livre.…”
Section: -Colesterol E 7-cetocolesterol Livresunclassified
“…Estudos que avaliaram o efeito do processamento térmico sobre a formação dos óxidos de colesterol em alimentos sugerem que o tempo e a temperatura são fatores determinantes neste processo, influenciando diretamente a taxa de oxidação [12,21,26,31].…”
Section: -Introduçãounclassified
See 1 more Smart Citation